Clostridium difficile and its cytotoxin in infants admitted to hospital with infectious gastroenteritis. Issue 6416 (18th February 1984) - Ellis, M E; Mandal, B K; Dunbar, E M; Bundell, K R
Abstract : During a prospective study of infectious gastroenteritis in children under 2 years, 19 out of 390 patients (4.9%) were found to have Clostridium difficile cytotoxin in the faeces. In several there was no history of use of antibiotics. The symptoms of many infants with toxin settled spontaneously, but one child became acutely and severely ill and developed a toxic megacolon and five others required, and responded to, vancomycin. Cl difficile was cultured from the stools in 191 (49%) of the children. The highly significant increased prevalence of past use of antibiotics in 118 control patients was not associated with an increased incidence of either isolation of Cl difficile or presence of faecal cytotoxin. Cl difficile should not be overlooked as a cause of acute diarrhoea and vomiting in children under 2 years.